2019
DOI: 10.1002/mame.201900107
|View full text |Cite
|
Sign up to set email alerts
|

Morphology Evolutions and Mechanical Properties of In Situ Fibrillar Polylactic Acid/Thermoplastic Polyurethane Blends Fabricated by Fused Deposition Modeling

Abstract: There are many studies devoted to conquer the strength–ductility trade‐off dilemma of polylactic acid (PLA) by flexible elastomer blending, like thermoplastic polyurethane (TPU), but little is known about the effects of the fused deposition modeling (FDM) process on the in situ morphology evolution of the elastomers. In this work, the effects of the three successive drawing processes in FDM on the morphology evolution of the dispersed TPU in the PLA matrix, and the toughening behavior of FDM‐printed PLA/microf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 59 publications
1
15
0
Order By: Relevance
“…[43] Qian et al [44] also reported that the strength and stiffness, as well as the impact strength of PLA/TPU blends, could noticeably be improved with the incorporation of 20 wt% short carbon fibers. Recently, with in situ fibrillation of TPU in PLA/TPU blends, improvements in the toughness of printed structures were reported due to the generation of TPU fibrils, enhanced PLA crystallization around the fibrillated structures, and hence improved interfacial interactions [45] Considering the long-term behavior of PLA/TPU blends, it has been reported that weathering could cause drastic losses in the strength and toughness of the blends. [46] It is still not very clear in the literature how changes in the TPU molecular structure such as variations in HS content or in the molecular weight of SS could influence the final properties of PLA/TPU blend systems.…”
Section: Introductionmentioning
confidence: 99%
“…[43] Qian et al [44] also reported that the strength and stiffness, as well as the impact strength of PLA/TPU blends, could noticeably be improved with the incorporation of 20 wt% short carbon fibers. Recently, with in situ fibrillation of TPU in PLA/TPU blends, improvements in the toughness of printed structures were reported due to the generation of TPU fibrils, enhanced PLA crystallization around the fibrillated structures, and hence improved interfacial interactions [45] Considering the long-term behavior of PLA/TPU blends, it has been reported that weathering could cause drastic losses in the strength and toughness of the blends. [46] It is still not very clear in the literature how changes in the TPU molecular structure such as variations in HS content or in the molecular weight of SS could influence the final properties of PLA/TPU blend systems.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the morphological and mechanical properties of PLA/TPU blends with and without using a compatibilizer 43–61 . Although some studies have reported that PLA and TPU are not compatible, 43–45 a few studies have shown that the ductility and impact strength of the PLA/TPU blends could be improved to some extent without the use of a compatibilizer while the strength and modulus were also decreased 44–49 .…”
Section: Introductionmentioning
confidence: 99%
“…PLA has been authorized by the Food and Drug Administration (FDA) for many clinical applications and is considered as an ideal choice for biomedical material. [ 9–12 ] However, the wide application of PLA is limited by its brittleness. [ 9,13 ] Absorbable thermoplastic polyurethane (TPU) is an ideal elastomer with mechanical properties.…”
Section: Introductionmentioning
confidence: 99%